Philippines - Transport for Growth : An Institutional Assessment of Transport Infrastructure - World Bank (World Bank, 2012)
Infrastructure needs in the Philippines must be addressed to ensure long term economic growth. After several years of fiscal pressure, the Philippines is now in a position to address these needs. Despite the current international financial situation, the country is now in a position to commit resources to improve transport infrastructure. To this effect, it is necessary to: i) make resource allocation more effective; and ii) improve governance in the coordinating departments and in implementation agencies. The suggested actions that follow address these two fundamental needs within four groups of recommendations. First, focus should be on improving infrastructure quality and service delivery. While the quantity of transport infrastructure in the Philippines in network and facility density compares well with other countries in the region, its capacity and quality does not. Some critical transport costs are higher in the Philippines than in its neighboring and competing countries. Second, the processes for allocating public resources could be improved. With additional public resources available, project preparation, planning and budget processes need to ensure that expenditures are well focused on areas that offer the best value for money in improving service quality. The government has taken important initiatives to achieve this end. But much remains to be done. The quality of multiyear planning and the quality of project preparation and selection in the annual budgetary process could be improved. Third, higher public spending on transport infrastructure will be effective only if accompanied by a program to confront institutional and policy distortions. In national budgeting and planning processes, this means improving the quality of planning documents and project appraisal and strengthening of prioritization in the national planning. Fourth, the private sector could be encouraged to continue its important role in transport infrastructure investment. Public resources alone will not meet the financing needs. In the mid-1990s the Philippines experienced a rich supply of proposals for private finance, mostly unsolicited. Often poorly coordinated with other facilities, these initiatives met with mixed success.